O2, NO2 and NH3 coordination to Co-porphyrin studied with scanning tunneling microscopy on Au(111). Issue 17 (16th April 2019) - Chang, Min Hui; Kim, Na-Young; Chang, Yun Hee; Lee, Yeunhee; Jeon, Un Seung; Kim, Howon; Kim, Yong-Hyun; Kahng, Se-Jong
Abstract : We observed a square ring structure in O2, a rectangular ring structure in NO2, and a bright-center structure in NH3 coordinated to Co-porphyrin. Abstract : The coordination structure between small molecules and metalloporphyrins plays a crucial role in functional reactions such as bio-oxidation and catalytic activation. Their vertical, tilting, and dynamic structures have been actively studied with diffraction and resonance spectroscopy for the past four decades. Contrastingly, real-space visualization beyond simple protrusion and depression is relatively rare. In this paper, high-resolution scanning tunnelling microscopy (STM) images are presented of di-, tri-, and tetra-atomic small molecules (O2, NO2, and NH3, respectively) coordinated to Co-porphyrin on Au(111). A square ring structure was observed for O2, a rectangular ring structure for NO2, and a bright-center structure for NH3 at 80 K. The symmetries of experimental STM images were reproduced in density functional theory (DFT) calculations, considering the precession motion of the small molecules. Thus, this study shows that the structure of small molecules coordinated to metalloporphyrins can be visualized using high-resolution STM and DFT calculations.